Optimization methods of replenishment of material base of agriculture (Journal of Economic Research & Business Administration, 2016)
The article discusses the current state of agricultural production, in- adequate technical security of rural producers, analyzed the development of technical equipment of rural enterprises, made a calculation of the re- quired composition of technical base of agricultural production by apply- ing a regression equation on the imputation principle of optimization of structure of technical resources. Also in the ways of the agroservice enter- prises, where the concentration of modern machines used to perform time- consuming and responsible work that is not able to carry out individual farms.
Keywords: agricultural production; technical resources; security; physical infrastructure; agricultural enterprises; efficiency; optimization; development; improvement